The spectral sensitivity of Drosophila photoreceptors. - Sharkey, C.R.; Blanco, J.; Leibowitz, M.M.; Pinto-Benito, D.; Wardill, T.J. (Scientific reports, 2020)
Drosophila melanogaster has long been a popular model insect species, due in large part to the availability of genetic tools and is fast becoming the model for insect colour vision. Key to understanding colour reception in Drosophila is in-depth knowledge of spectral inputs and downstream neural processing. While recent studies have sparked renewed interest in colour processing in Drosophila, photoreceptor spectral sensitivity measurements have yet to be carried out in vivo. We have fully characterised the spectral input to the motion and colour vision pathways, and directly measured the effects of spectral modulating factors, screening pigment density and carotenoid-based ocular pigments. All receptor sensitivities had significant shifts in spectral sensitivity compared to previous measurements. Notably, the spectral range of the Rh6 visual pigment is substantially broadened and its peak sensitivity is shifted by 92 nm from 508 to 600 nm. We show that this deviation can be explained by transmission of long wavelengths through the red screening pigment and by the presence of the blue-absorbing filter in the R7y receptors. Further, we tested direct interactions between inner and outer photoreceptors using selective recovery of activity in photoreceptor pairs.